Masquelet technique combined with a lantern-mimicking frame system for treatment of a 28-cm infected bone defect: a case report - Qv, Ji; Gu, Feng; Wang, Yanbing; Peng, Chuangang; Wu, Dankai (Frontiers in Surgery, 2025)
IntroductionTreatment of large bone defects resulting from acute injury or infection remains challenging. The Masquelet technique is a two-stage procedure for treating bone defects caused by bone tumor resection, infection, or trauma. There are currently no reports of successful repair of ≥28 cm bone defects using the Masquelet technique.Case presentationWe describe the case of a 55-year-old man with postoperative infection of a femoral fracture and a 28-cm infected bone defect formed after multiple debridement procedures. The Masquelet technique, when coupled with a Lantern-Mimicking Frame System (LMFS), achieved favorable clinical results. The patient could walk normally without crutches 14 months postoperatively and did not experience pain in daily life.ConclusionsThis was the longest bone defect in a single limb currently reported to had been cured in the literature. The Masquelet technique coupled with LMFS achieved favorable clinical results for the treatment of a 28-cm infected bone defect. For extremely large bone defects in a single limb, the length of the defect was not an absolute limiting condition for the indications of Masquelet technique.